An analysis of violent music lyric contents towards students' physical and emotional aggression / Dilyla Khalid - Khalid, Dilyla (Faculty of Music, 2017)
This paper educates the younger generations that is exposed to such violent content and to what extend does this content affects their physical and emotional state of aggressions. Having a huge number of songs with violent lyrical content being release to the public, the younger generations may be fragile to such content, because of the little study being done in Malaysia on violent lyric content in songs, research on this matter is important. In which, violent lyric content may be an "arousal and provocation of may be of potential response by their listeners" (Johnson. B. and Cloonan. M, 2009). In contrast to the usual conditions of reading a book and viewing paintings, the audience or listeners especially in the current pop era may well be effected by music with violent lyrical content as listening to music has become part of their daily routine. This study also elaborate on how musical experience might effects the changes in youngsters behaviours and is it crucial that we investigate the reason that may triggers while listening to such music.